The Effect of Solid Organic Fertilizer and Liquid Cow Dung Fertilizer on Rice Growth (Oryza Sativa L) - Saragih, Meylin Kristina; Panataria, Lince Romauli; Sitorus, Efbertias (Journal of Agriculture, 2024)
This research was conducted in Sei Beras Sekata Village, Sunggal District, Deli Serdang Regency, North Sumatra Province. With an altitude of ± 25 meters above sea level. This study aimed to determine the response of rice growth (Oryza sativa L) to the provision of cow manure and liquid fertilizer. The design used was a Randomized Block Design (RAK) Factorial with the main treatment being solid organic fertilizer (A) with three treatments, namely L1 = (660 gr / Plot) 3 tons / Ha, L2 = (1100 gr / Plot) 5 tons / Ha, L3 = (1650gr / Plot) 7.5 tons / Ha. Organic fertilizer 3 treatments, namely, K1 = 2.5cc / liter, K2 = 5cc / liter, K3 = 7cc / liter. The parameters observed in this study were plant height per clump (cm), number of tillers per clump (stem), and number of productive tillers per clump (stem). The study showed that solid organic fertilizer treatment had no significant effect on all parameters. In contrast, liquid organic fertilizer significantly affected the number of productive shoots but did not significantly affect plant height per clump (cm) and number of shoots per clump (stems).